Positive Negative Affect and Teen Pregnancy - Istiqomah Istiqomah (Proceedings Series on Social Sciences & Humanities, 2021)
Pregnancy is one of the important events in a woman’s life. Having a positive and planned pregnancy will impact the psychological well-being of both mother and baby. This study describes the relationship between the affect and demographics of pregnant adolescents. Respondents consisted of 92 pregnant adolescents (19.6% trimester 1, 41.3% trimester 2 and 39.1% trimester 3), with an age range of 16 to 35 years (M = 18.99, SD = 2.899). Pregnant adolescents were asked to fill in the positive and negative influence scale (PANAS). The correlation coefficient of Cronbach’s alpha for the positive influence scale is 0.845. The correlation coefficient of Cronbach’s alpha for the negative influence scale is 0.676. Researchers used Chi-Square to determine the relationship between positive and negative influences with the demographic characteristics of adolescent mothers. The results of the description of the Positive affect were related to age (Asymp. Sig. = 0.000) and gestational age (Asymp. Sig. = 0.009). In contrast, the Negative affect was related to adolescent education (Asymp. Sig. = 0.013). These results underlie the process of adaptation of adolescent mothers in undergoing a healthy and planned pregnancy.